The development of a financial model to predict business performance of IBS construction company based on selected financial ratios / Norazuaniza Mohd Yunus - Mohd Yunus, Norazuaniza (2015)
The utilization o f Industrialized Building System (IBS) in the construction industry give benefits to the construction industry players which includes minimizing the employment o f foreign labors, reduces the time and cost o f the project, also contribute to the construction waste reduction. Though the government o f Malaysia has given the incentives by exemption o f levy equal to 0.125 percent o f total project cost if the contractor use up to 70 percent IBS component (especially for government building) in their project, there still poor participation from contractors to get engage in the IBS nature o f business. Aware to the situation, this research presents the development of financial mathematical model to predict the business performance o f the IBS construction company using the selected financial ratio. This study also introduced the work involved in the development o f a model based on the financial parameters from the historical financial statement to help the construction company predict their business performance when they embrace the IBS project in the future. The parameters o f the financial model are the selected financial ratios obtained from the financial statements gathered from thirty (30) IBS companies in Selangor. These financial statements collected from the annual accounting report spanning from 2006 until 2009 provided by the Companies Commission of Malaysia (CCM). Analysis using multiple linear regression to fit the selected financial ratios that form the model was done using the matrix solution o f the Matlab software. The model is then validated with the actual company’s business performance. IBS ConstructionCompany or any interested parties could use the model to predict their own business performance as additional information for their decision making purposes.